Чи можна знайти гробницю Олександра Македонського? - Мальований, О.М. (Археологія, 1998)
Залучаючи писемні джерела автор піддає сумніву спроби грецької дослідниці Ліани Суваліді знайти гробницю Олександра Македонського в руїнах храму Амона в районі оазісу Сіва. В статье автор попытался доказать, что Александр Македонский не был похоронен где-либо в другом месте, кроме Александрии Египетской, что старается опровергнуть греческая экспедиция во главе с Лианой Сувалиди. Свое мнение автор подкрепляет анализом античных источников, пишущих о смерти и погребении античного полководца. Но и в Александрии, считает автор, найти останки его мавзолея или (что важнее) саркофага и мумии не удастся, скорее всего, никогда из-за стихийных бедствий, обрушившихся на город, а также разрушительных исторических событий, пронесшихся за время его существования. Кроме античных авторов использованы труды историков нового времени. The author of the paper tries to prove that Alexander Macedonian was buried in no other place as in Alexandria of Egypt. The Greek expedition headed by Liana Suvalidi attempts to refute that idea. The author confirms his opinion by the analysis of antique sources, which provide data about the death and funeral of the great general. In addition to antique authors, the author uses works of historians of the new time. But the author thinks that most likely it is impossible to find the remnants of Alexander Macedonian’s mausoleum or (which is even more important) of the sarcophagus and mummy as there were many disasters that fell on the town and many destructive historical events that blew over the town for the years of its existence.